2008
DOI: 10.1124/mol.108.048611
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heme Oxygenase-1 Protects Dopaminergic Neurons against 1-Methyl-4-Phenylpyridinium-Induced Neurotoxicity

Abstract: Heme oxygenase-1 (HO-1) is up-regulated in response to oxidative stress and catalyzes the degradation of pro-oxidant heme to carbon monoxide (CO), iron, and bilirubin. Intense HO-1 immunostaining in the Parkinsonian brain is demonstrated, indicating that HO-1 may be involved in the pathogenesis of Parkinsonism. We here locally injected adenovirus containing human HO-1 gene (Ad-HO-1) into rat substantia nigra concomitantly with 1-methyl-4-phenylpyridinium (MPP(+)). Seven days after injection of MPP(+) and Ad-HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 37 publications
4
81
0
Order By: Relevance
“…It is established that expression levels or the activity of HO-1 and GPx are involved in the elimination or inactivation of ROS [35], and that this effect is mediated by activation of NRF2 [36]. Although normal tissues express extremely low basal levels of HO-1 protein [37,38], diabetic rats receiving antioxidant treatment have significantly increased HO-1 protein levels compared with normal controls [39]. Together, our data suggest that the expression of HO-1 protein may be a key factor in preventing mice from developing renal lesions in DN.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that expression levels or the activity of HO-1 and GPx are involved in the elimination or inactivation of ROS [35], and that this effect is mediated by activation of NRF2 [36]. Although normal tissues express extremely low basal levels of HO-1 protein [37,38], diabetic rats receiving antioxidant treatment have significantly increased HO-1 protein levels compared with normal controls [39]. Together, our data suggest that the expression of HO-1 protein may be a key factor in preventing mice from developing renal lesions in DN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CO exerts cytoprotective effects through its potent anti-inflammatory, anti-apoptotic, and vasodilatory properties. 4,18) Bile pigments biliverdin and bilirubin are peroxy radical scavengers. 5) However, some studies suggested that HO-1 induction might not always be beneficial and the release of redox-active iron from heme might enhance oxidative stress.…”
Section: )mentioning
confidence: 99%
“…18) We examined the effects of EPS on HO-1 expression using the human neuroblastoma cell line SH-SY5Y, which is a model of neuronal cells. SH-SY5Y cells were treated with EPS at 10, 50, and 100 µM for 24 h. EPS at those concentrations had no effect on cell viability (data not shown).…”
Section: Effect Of Eps On Ho-1 Levels and Nrf2 In Sh-sy5y Cellsmentioning
confidence: 99%
“…It has been widely reported that HO-1 plays a crucial role in maintaining redox homeostasis during cellular stress (11)(12)(13). Increased HO-1 expression contributes to promoting the degradation of heme into carbon monoxide and biliverdin, the latter being the immediate precursor of the powerful antioxidant molecule bilirubin (14).…”
Section: Introductionmentioning
confidence: 99%